Persaingan Pemasaran Mengenai Kuliatas Produk Dan Jaringan Bisnis Pada Karsa Mahardika Nusantara - Resya Dwi Marselina; Ayu Wandira; Broderix Nicender; Ilham Muharman; Wahyudin Yusuf (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This article aims to determine marketing competition regarding product quality and business networks at Karsa Mahardika Nusantara. This research focuses on the marketing and quality of products and business networks that have been carried out by Karsa Mahardika Nusantara. Observation and interviews are data collection techniques in this research. Based on the results of this research analysis, it can be concluded that Karsa Mahardika Nusantara has done marketing well and is able to compete with similar competitors, even though they have to expand their marketing area, Karsa Mahardika Nusantara is confident in the quality and materials they have so that they continue to grow and develop well until now.